Cross-sectional and prospective associations between stress, perseverative cognition and health behaviours. Issue 1 (7th January 2022) - Clancy, Faye; Prestwich, Andrew; Ferguson, Eamonn; O'Connor, Daryl B.
Abstract: Objectives: The Perseverative Cognition Hypothesis (proposing negative repetitive thinking has detrimental effects on physical health), has been extended to include health behaviours. This study aimed to examine relationships between perseverative cognition, stress and health behaviours. Design: Participants ( n = 336) completed online surveys twice, 3 months apart. Main outcome measures: Cross-sectional and prospective associations between perseverative cognition (worry, brooding and reflection), stress and health behaviours (sleep, diet, physical activity and alcohol). Results: Analyses demonstrated associations between worry, brooding and reflection and health behaviours, cross-sectionally and prospectively, including sleep and unhealthy snacking. Adding perseverative cognition variables to models simultaneously, only two associations remained (brooding and unhealthy snacking, worry and poorer sleep quality). Controlling for stress, only the cross-sectional association between brooding and more unhealthy snacking remained significant and no significant interactions with stress were found. Conclusion: This study evidences associations between components of perseverative cognition and health behaviours cross-sectionally and prospectively.